PENGEMBANGAN SEL SURYA BERPEWARNA TERSENSITISASI(DYE SENSITIZED SOLAR CELL) DENGAN SENYAWA MORIN DARIKAYU NANGKA (ARTOCARPUS HETEROPHYLLUS L.) - Dwi Rahayu, Adhitya Bagitaningtyas, Arif Hidayat, dan Atin Suci P. (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
The research were aimed at synthesizing morin synthesized TiO2 from the wood of jackfruit as DSSCmaterial, finding out the characters of the compound produced in various calcination temperatures andthe gap energy produced by the material.The morin extract in the ethanol was obtained from the maceration process of dry jackfruit wood,whereas TiO2 was produced through the reaction of base deposition of TiCl4 and H2O2 in thetemperature of 200oC by using NaOH 10 M base. The mixture of TiO2 and morin produced DSSCmaterial. The characterization of DSSC material was conducted by using XRD, while the gap energy wasdetermined by using visible light spectrophotometer.The morin compound as the result of the extraction of jackfruit wood had a maximum absorption inthe wave length of 280 nm. TiO2 crystal calcinated in the temperature of 500oC and 700oC did not showthe formation of anatase phase. Crystal TiO2 as the result of the synthesis in the calcinationstemperature of 900oC showed the mixture of anatase and TiO2 (B). the addition of morin as asynthesizer in DSSC did not cause a change of composition in TiO2, the result of synthesis. The gapenergy of Morin synthesized TiO2 was 2.82 eV with the optimum absorption in the wave length of 440nm.Key words: DSSC, Morin, jackfruit wood, TiO2